MODEL PEMBELAJARAN BERBASIS PROJECT BASED LEARNING PADA MATA PELAJARAN AGAMA KRISTEN - alex kristiawan zalukhu; Jon Jon; Eni Rombe (STT Kristus Alfa Omega, 2023)
The research objectives are: To determine the level of implementation of Project Based Learning based learning model on Christian religious subjects for students in class X-XII SMK Negeri 3 Lahewa. This study uses quantitative descriptive research, which aims to provide an overview of the implementation of Project Based Learning-based learning models on Christian religious subjects for students in class XXII of SMK Negeri 3 Lahewa. Where the data collection technique using a questionnaire or questionnaire. The results of the hypothesis test; Ho is accepted and Ha is rejected. Because the value of the hypothesis (µ0) 60% or equal to 51, is not the same as the value of the empirical score or smaller, namely 45.29. And the variable value of the implementation of Project Based Learning based learning model on Christian religious subjects in class X-XII SMK Negeri 3 Lahewa obtained 53.29 in the medium category (41-60).